2013
DOI: 10.1159/000350321
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Polyposis following Abdominal Colectomy and Helicobacter pylori Eradication for Cronkhite-Canada Syndrome

Abstract: The etiology of Cronkhite-Canada syndrome (CCS) remains unknown and many cases are refractory to treatment. Therefore, new therapies are urgently needed. Furthermore, a number of CCS cases with gastrointestinal carcinoma have been reported. Our patient had rapid onset of CCS and early development of colon carcinoma associated with adenomas. High anterior resection of the sigmoid colon and ileostomy were performed, and her symptoms and endoscopic and histological findings improved. Helicobacter pylori eradicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Numerous treatment approaches, including aggressive nutritional support,14 100 101 antibiotics,8 42 histamine receptor antagonists,14 cromolyn sodium,14 immune suppression (corticosteroids, azathioprine and cyclosporine),13 20 102 103 and surgery89 104 105—often in different combinations—have had variable success 4 6 100 102 106. Apart from nutritional support, corticosteroids are currently recommended as the mainstay of medical treatment,26 with azathioprine used for its steroid-sparing effect 13.…”
Section: Therapy and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous treatment approaches, including aggressive nutritional support,14 100 101 antibiotics,8 42 histamine receptor antagonists,14 cromolyn sodium,14 immune suppression (corticosteroids, azathioprine and cyclosporine),13 20 102 103 and surgery89 104 105—often in different combinations—have had variable success 4 6 100 102 106. Apart from nutritional support, corticosteroids are currently recommended as the mainstay of medical treatment,26 with azathioprine used for its steroid-sparing effect 13.…”
Section: Therapy and Outcomementioning
confidence: 99%
“…CCS has an extremely variable clinical course, ranging from fulminant cases to those with initial remission of GI as well as systemic manifestations (occurring spontaneously or after therapy) 42 92 103 106 108–113. Less than 5% of patients have a complete remission, however, and overall outcome remains poor 114.…”
Section: Therapy and Outcomementioning
confidence: 99%
“…In addition, Goto et al [5] reported that mental stress and physical fatigue were the important risk factors for CCS. HP might also another factor since eradication of HP could reduce some symptoms in CCS patients [14,15]. There is very limited information in our study.…”
Section: Discussionmentioning
confidence: 78%
“…Treatment responses to corticosteroids or azathioprine also suggest possible underlying autoimmune mechanism. H. pylori infection was also reported to be related, and eradication of H. pylori seems to improve symptoms in some cases [9] [10].…”
Section: Discussionmentioning
confidence: 99%